Effect of the increasing use of coronary angioplasty on outcome at one year in patients with unstable angina. Issue 6 (December 1995) - De Servi, S.; Valentini, P.; Angoli, L.; Bramucci, E.; Barberis, P.; Mariani, G.; Specchia, G.
Abstract : OBJECTIVE--To determine whether the increasing use of percutaneous transluminal angioplasty in patients with unstable angina has reduced the need for bypass surgery and whether this change in the choice of treatment affected the outcome at one year in patients with unstable angina who were admitted to hospital in two different periods of time. DESIGN--Retrospective analysis of consecutive patients with unstable angina (angina at rest with ST-T changes during pain) who underwent coronary arteriography in two different periods of time. PATIENTS--158 patients were admitted to hospital between January 1988 and June 1989 (group 1) and 140 patients admitted between January 1992 and June 1993 (group 2). RESULTS--Coronary angioplasty procedures nearly doubled from 29% in group 1 to 56% in group 2 whereas bypass surgery decreased from 36% in group 1 to 23% in group 2 (P < 0.01). Coronary angioplasty increased and bypass surgery decreased in patients with one vessel disease (P < 0.01), two vessel disease (P < 0.05), and three vessel disease (P < 0.01). Coronary angioplasty also increased and bypass surgery decreased in refractory angina and in patients with ejection fraction < 0.50 (both P < 0.05). At 1-year follow up, 14 patients in group 1 (9%) and 10 in group 2 (7%) either died or had myocardial infarction (P = NS). Revascularisation procedures were needed in 16 group 1 patients (10%) and 27 group 2 patients (19%, P < 0.05). CONCLUSIONS--Coronary angioplasty became more widely used in patients with unstable angina. This reduced the need for bypass surgery in patients with multivessel disease, refractory angina, and depressed left ventricular function. This change in treatment did not affect 1-year mortality or the myocardial infarction rate. More patients in the more recent group in which angioplasty was the preferred treatment required a further revascularisation procedure than in the earlier group in which bypass grafting was more often used as the initial treatment.